The effect of financial literacy : investment decisions among university students - Ton, My Linh (2017)
Amid the development of financial markets, there is a growing concern that individuals do not possess a corresponding level of literacy to deal with the diversity and complexity of financial products, which is especially prominent among the young adults. Hence, this study is driven to investigate the effect of financial literacy on investment decisions, by inviting 400 students from Nanyang Technological University, Singapore, to participate in a hypothetical investment game. Capitalising on Ordinary Least Square (OLS) regression model, findings connote that students from business faculties exhibit a higher level of financial literacy. As predicted, financial literacy is also underscored to have a momentous effect on individual's investment performance. In addition, the results also demonstrate faculty, gender, and risk attitude as crucial determinants of financial literacy.